Analisis Ameliorasi Dalam Novel “Tuhan Izinkan Aku Menjadi Pelacur” Karya Muhidin M. Dahlan - Katharina Woli Namang; Sintya Rahmawati Dewi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Changes in meaning are influenced by the development of the times due to several factors. Changes in meaning can also occur in the world of literature, because literature is created using the medium of language. Language is a social creation, one of the literary works is the novel. Lord Of The Rings let me be a goddamn whore. Dahlan is an interesting novel because the story is taken from the real events of a Muslim woman who was very devout worship and then became a prostitute. In the middle of the process of becoming a kaffah/total muslimah, hit by a storm of disappointment by the organization she adored so that she finally decided to get out/run away. It is in that empty state that falls into a black world. The purpose of this study was to examine the changes in the form of amelioration in the novel God allow me to be a prostitute by Muhidin M. Dahlan. This type of research is a descriptive qualitative research. The Data in this study are words derived from novel quotations, and the source of the data in this study is the novel God allow me to be a Whore By Muhidin M. Dahlan. Data collection techniques used in this study are read and record. Data analysis techniques by classifying data including amelioration, marking the words, analyzing the data in accordance with the Indonesian dictionary (KBBI) and making conclusions. The results of this study, found as many as 30 word forms that change the meaning of amelioration.